1989
DOI: 10.1128/jb.171.2.754-760.1989
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization, and expression in Escherichia coli of the Streptomyces clavuligerus gene encoding deacetoxycephalosporin C synthetase

Abstract: Biosynthesis of cephalosporin antibiotics involves an expansion of the five-membered thiazolidine ring of penicillin N to the six-membered dihydrothiazine ring of deacetoxycephalosporin C by a deacetoxycephalosporin C synthetase (DAOCS) enzyme activity. Hydroxylation of deacetoxycephalosporin C to form deacetylcephalosporin C by a deacetylcephalosporin C synthetase (DACS) activity is the next step in biosynthesis of cephalosporins. In Cephalosporium acremonium, both of these catalytic activities are exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 21 publications
2
72
0
Order By: Relevance
“…Three hybridizing lambda clones (F, G, and H [not shown]) were isolated. The insert DNA from clone F hybridized to clone E DNA, and results of further restriction mapping of the putative cefE DNA were consistent with published maps of the region (8,9). This indicated that the synthetic cejE probe had indeed hybridized with the cefE gene in our library and showed that the putative lat gene was approximately midway between pcbC and cefE (Fig.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Three hybridizing lambda clones (F, G, and H [not shown]) were isolated. The insert DNA from clone F hybridized to clone E DNA, and results of further restriction mapping of the putative cefE DNA were consistent with published maps of the region (8,9). This indicated that the synthetic cejE probe had indeed hybridized with the cefE gene in our library and showed that the putative lat gene was approximately midway between pcbC and cefE (Fig.…”
Section: Resultssupporting
confidence: 67%
“…1). To position lat relative to the DAOCS gene, cefE, the S. clavuligerus genomic library was probed with a 33-mer synthetic oligonucleotide, the sequence of which was that of the 5' terminal 11 codons in the published sequence of the DAOCS gene (9). Three hybridizing lambda clones (F, G, and H [not shown]) were isolated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NdeI-BamHI fragment from pOW1067 containing penDE was subsequently subcloned into an E. coli expression vector containing the k PL promoter, creating pOW233. E. coli L201 cells containing this plasmid were induced for protein production (12,21). After 6 h, protein-containing granules were observed by phasecontrast microscopy.…”
Section: Resultsmentioning
confidence: 99%